2015
DOI: 10.4103/0972-124x.153475
|View full text |Cite|
|
Sign up to set email alerts
|

Pre-emptive 8 mg dexamethasone and 120 mg etoricoxib for pain prevention after periodontal surgery: A randomised controlled clinical trial

Abstract: Several anti-inflammatory drugs have been used to reduce pain and discomfort after periodontal surgeries. This study evaluates the efficacy of using etoricoxib and dexamethasone for pain prevention after open-flap debridement surgery. In this study, 60 patients who were undergoing open flap debridment surgery were randomly assigned to receive a single dose preoperative medication 1 hour prior to surgery. The patients were divided into three groups. In Group 1, 20 patients were given placebo drug orally. In Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 16 publications
(19 reference statements)
0
23
0
Order By: Relevance
“…Through both databases, 149 scientific articles were identified. This revision did not include clinical trials using etoricoxib in endodontics or periodontics, as well as those studies comparing etoricoxib with an active control other than NSAIDs [33][34][35][36][37]. After excluding duplicate reports and considering the focus of this review, 11 papers fulfilled the PICO strategy (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Through both databases, 149 scientific articles were identified. This revision did not include clinical trials using etoricoxib in endodontics or periodontics, as well as those studies comparing etoricoxib with an active control other than NSAIDs [33][34][35][36][37]. After excluding duplicate reports and considering the focus of this review, 11 papers fulfilled the PICO strategy (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, no studies evaluating the preemptive effects of nimesulide in periodontal surgeries were found. Studies on preemptive analgesia in periodontal surgeries have used different steroidal and non‐steroidal drugs, such as dexamethasone, eterocoxib, and celocoxib 15,27,37,38 . Overall, results showed beneficial effects of preemptive analgesia on pain control and on the quantity of rescue medication when compared to the use of placebo.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies, patients who needed to take backup medication were excluded from the analysis [18,30]. In most cases, patients who needed backup medication were part of placebo group [15,19,23,25,26,[31][32][33].…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…The methodological quality of each study was classified as low, high, or some concerns. A substantial risk of bias was determined for 9 studies [14,15,17,20,29,31,[38][39][40], some concerns for one study [28], and a low risk of bias for the others.…”
Section: Risk Of Biasmentioning
confidence: 99%